Implikasi Teologi Islam Transformatif Terhadap Teologi, Sosiologis, Politik dan Ekonomi - Ali Hasan Siswanto; Maya Hilmi Amalia; Imtiyaz Mustafidatul Wasi'ah; Meirisa Nurjannah (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Transformative Islamic theology, developed by Moeslim Abdurrahman and a number of Indonesian Islamic studies writers, emphasizes that faith should not be limited to theory but must be able to penetrate social, political, and economic structures to realize justice and concern for the oppressed. However, much research on its implications remains fragmented: theological, social, political, and economic life are discussed separately, so that the deep connections between these dimensions have not been systematically and analytically examined. This article aims to fill this gap by developing a theoretical-analytical framework for how transformative Islamic theology simultaneously influences these four domains of life. The theoretical approach used is a synthesis of transformative theology, modern social theory, participatory political theory, and economic justice theory, utilizing classical Islamic and modern texts, as well as contemporary empirical studies. Qualitative research methods using textual analysis and case studies are used to explore the implications of transformative theology at the levels of belief, social relations, politics, and the economy. The main argument of this article is that transformative theology can transform theological patterns (inclusive understanding, critique of absolute power), social patterns (equality relations between groups), political patterns (more inclusive political participation), and economic patterns (tendencies toward distributive justice, zakat, waqf, and sharia economics). The greatest scholarly contribution is the strengthening of the "implications of transformative theology" model, which connects theological dimensions with socio-political-economic structures, so that Islamic studies do not stop at the normative level but become a framework for contemporary social interpretation.